2013
DOI: 10.1371/journal.ppat.1003734
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosis Type VII Secreted Effector EsxH Targets Host ESCRT to Impair Trafficking

Abstract: Mycobacterium tuberculosis (Mtb) disrupts anti-microbial pathways of macrophages, cells that normally kill bacteria. Over 40 years ago, D'Arcy Hart showed that Mtb avoids delivery to lysosomes, but the molecular mechanisms that allow Mtb to elude lysosomal degradation are poorly understood. Specialized secretion systems are often used by bacterial pathogens to translocate effectors that target the host, and Mtb encodes type VII secretion systems (TSSSs) that enable mycobacteria to secrete proteins across their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
192
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 161 publications
(201 citation statements)
references
References 68 publications
4
192
0
Order By: Relevance
“…Interestingly, esxG and esxH play a role in virulence beyond their requirement for iron acquisition (20). Consistent with these findings, we previously showed that the EsxG-EsxH complex from M. tuberculosis, but not that from the M. smegmatis EsxG-EsxH complex, targets the host hepatocyte growth factor-regulated tyrosine kinase substrate (Hrs), a component of the endosomal sorting complexes required for transport (ESCRT) (28). M. tuberculosis EsxG-EsxH inhibits ESCRT, which is required for phagosome maturation.…”
supporting
confidence: 57%
See 1 more Smart Citation
“…Interestingly, esxG and esxH play a role in virulence beyond their requirement for iron acquisition (20). Consistent with these findings, we previously showed that the EsxG-EsxH complex from M. tuberculosis, but not that from the M. smegmatis EsxG-EsxH complex, targets the host hepatocyte growth factor-regulated tyrosine kinase substrate (Hrs), a component of the endosomal sorting complexes required for transport (ESCRT) (28). M. tuberculosis EsxG-EsxH inhibits ESCRT, which is required for phagosome maturation.…”
supporting
confidence: 57%
“…EsxG Mt and EsxH Mt were expressed in tandem as a single polypeptide separated by a linker (GLVPRGSTG) as previously described (28 8.0) and incubated at room temperature for 40 min, followed by centrifugation at 10,000 ϫ g for 30 min at 4°C. The supernatant was incubated with nickel-nitrilotriacetic acid (Ni-NTA) Superflow resin (Qiagen) at 4°C for 1.5 h. The Ni-NTA resin was washed with lysis buffer containing up to 60 mM imidazole, followed by elution in lysis buffer containing 250 mM imidazole.…”
Section: Methodsmentioning
confidence: 99%
“…42 Importantly, perturbation of this process adversely affects phagosomal maturation and pathogen eradication. 43 The ESCRT (endosomal sorting complex required for transport) machinery consists of four complexes, ESCRT-0, -I, -II and -III, which operate sequentially to mediate MVB formation via three distinct but connected steps: capturing the ubiquitin-tagged cargo, deforming the phagosomal/endosomal membrane and membrane abscission from the inside. 44 The ubiquitin system has a central role in ESCRT-mediated MVB biogenesis.…”
Section: Function Of the Ubiquitin System In Phagosomal Maturation Dumentioning
confidence: 99%
“…Recently, it was shown that the secreted tyrosine phosphatase PtpA directly binds to the H subunit of the v-ATPase, resulting in the dephosphorylation of vacuolar protein sorting protein 33B (VPS33B) and subsequent impairment of v-ATPase recruitment to the vacuole (Wong et al 2011). It was also shown that M. tuberculosis uses its type VII secretion system ESX-3 to export two effector proteins-namely, EsxH and EsxG-that interact with Hrs and impair phagosome maturation through disrupting the endosomal sorting complex required for transport (ESCRT) (Mehra et al 2013). Other mycobacterial secreted proteins are proposed to interfere with the host cell vacuolar sorting machinery, as suggested, for example, by the aberrant trafficking of a M. tuberculosis mutant inactivated in the alternative secretion system component SecA2 (Sullivan et al 2012).…”
Section: Phagosome Maturation Arrestmentioning
confidence: 99%